What happens after HIV self-testing? Results from a longitudinal cohort of Chinese men who have sex with men - Tang, Weiming (BMC Infect Dis, 2019)
BACKGROUND: HIV self-testing (HIVST) is a promising approach to expand HIV testing. HIVST is a process in which a person performs an HIV test and interprets the result. Negative HIVST results may encourage men who have sex with men (MSM) to use HIV prevention services. The objective of this study was to examine behaviors (e.g., facility-based HIV testing, condom use) after a negative HIVST test result among Chinese MSM. METHODS: We collected data from MSM in eight Chinese cities over a 12-month period. This is a secondary analysis of longitudinal cohort data collected as part of an intervention trial to increase HIV testing. Men completed a survey that described sociodemographic information, sexual behaviors, HIV self-testing, and facility-based HIV testing. Men who completed at least one follow-up survey were included in this analysis. Generalized linear mixed models were used to evaluate whether HIVST increased subsequent facility-based HIV testing and consistent condom use. RESULTS: We included 1219 men. Most men (78.7%) were under 30 years old and had never been married (87.0%). 755 (61.9%) men tested for HIV and 593 (49.3%) men self-tested during the study period. At baseline, among men who had never been tested for HIV, 44.9% (314/699) initiated HIVST during the study period. HIVST was associated with subsequent facility-based testing (aOR of 1.87, 95% CI: 1.47–2.37). HIVST was also associated with subsequent consistent condom use (aOR = 1.53, 95% CI: 1.13–2.06). CONCLUSION: HIVST was associated with subsequent facility-based HIV testing and consistent condom use. HIVST may enhance uptake of related HIV prevention services at facilities, suggesting the need for more implementation research.